138 Clinical diagnosis and management of phaeochromocytoma (PCC) and paraganglioma (PGL) in children and young people (CYP): a national guideline. On behalf of the UK paediatric phaeochromocytoma and paraganglioma guideline development group (GDG). (December 2018) - Marks, SD; Katugampola, H; Quek, S; Yadav, P; Spoudeas, H; Harrison, B
Abstract : Background: PCC/PGL are rare in children with an annual incidence of 0.2 and 0.3 per million in the 5–9 and 10–14 year age groups respectively. Most result from a genetic predisposition and represent a significant management challenge. Aims: To provide the first interdisciplinary national management guidelines using the AGREEII framework for CYP with confirmed or suspected PCC/PGL, endorsed by the RCPCH, UKCCLG and BSPED. Methods: 113 PICO clinical questions were formulated by a specialist GDG. Literature searches conducted via Ovid MEDLINE and Cochrane Library identified 526 articles. Post filtering, 397 were reviewed using GRADE. Where evidence was lacking/conflicting, a two-stage Delphi consensus process was conducted. Results: 39 recommendations were made; 21 were sent to consensus and achieved agreement. The GDG recommended cases be managed in a specialist endocrine centre with tertiary paediatric oncology. The team should be specific, age-appropriate, multidisciplinary, and led by an experienced lead clinician. Clinical assessment and a three-generation family history should be used to identify genetically determined and familial cases, along with genetic testing. Peri-operative steroid replacement should be led by a nominated endocrinologist post bilateral adrenalectomy or cortical sparing surgery. A Critical Care setting will rapidly identify and treat hypocortisolism/adrenal crisis with stress-doses of steroid. Patients who have undergone adrenocortical sparing surgery should continue maintenance steroid replacement until adrenocortical reserve is tested postoperatively. Patients with SDHB mutations and VHL have a higher risk of recurrent disease and malignancy; however, all cases of PCC/PGL should have life-long follow up. Conclusions: These guidelines provide the first evidence and consensus-based national recommendations for management of PCC/PGL in CYP and highlight a need for further audit and research. Implementation should improve the management and survival of CYP with PCC/PGL.